(untitled) (Politeja, 2017)
The purpose of the article is to present the multifaceted issue that is missile defense in the context of Polish safety. The fact that Poland is a member of NATO, but also its geographical location and the nature of potential security risks, mean that its position in terms of missile defense is not equivalent to that of other countries. In the case of Poland, we are dealing with plans to create a broadly understood air defense system; a compromise solution, the result of irreconcilable requirements, in which missile defense will be just one of many tasks rather than a priority.